PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASI DALAM MENINGKATKAN KINERJAKARYAWAN (STUDI PADA BIRO LINGKUP UNIVERSITAS PANCA SAKTI BEKASI) - Nova Rina (Sekolah Tinggi Manajemen IMMI, 2019)
This research seeks to examine the effect of leadership style and organization on organizational commitment in improving employee performance at the Bureau of the Panca Sakti University Bekasi.This research uses proportional random sampling method and the information used in this research is primary information in the form of a questionnaire. The research population amounted to 91 people. On the other hand, the illustration of this research is 40 people. The analytical method used in this study is the Structural Equation (SEM) method from the AMOS 4.0 application. The results of this study show that the cause and effect between the variables that influence the criteria for Goodness of Fit, namely chi square = ( 1144, 691 ) ; Probability=( 0, 058); CMIN/ DF=( 1,069), GFI=( 0, 826); AGFI=( 0, 809); TLI=( 0, 991); CFI=( 0, 992); RMSEA=( 0.017).The results of the study prove that leadership style has a positive and significant effect on organizational culture, leadership style has a positive and significant impact on organizational commitment, organizational culture has a positive and significant impact on organizational commitment, organizational commitment has a positive and significant impact on employee performance, and leadership style has a positive and significant influence on organizational commitment. on employee performance, and organizational culture that has a positive and significant impact on employee performance.If these findings are developed to improve employee performance, the Bureau of the scope of Panca Sakti University Bekasi needs to look at the factors that affect employee performance, such as leadership style, work culture, and commitment. Because knowing this influence can be used as a reference for designing strategies to improve employee performance.